Bibliometric analysis and systematic review of digital competence in education - Ma, Huiling; Ismail, Lilliati (Springer Nature, 2025)
The ubiquity of digital technologies has profoundly transformed communication and education in the 21st century, making the development of digital competence essential for both teachers and students to be prepared for the digital age. However, existing reviews predominantly focus on the teachers’ perspective with a limited scope and methodology. This literature review combines bibliometric analysis and systematic literature review to provide a comprehensive analysis of existing research. Bibliometric analysis evaluates performance and science mapping to identify influential journals, countries, and authors while visualizing trends in the field. Content analysis identifies five major themes: (1) digital competence levels, (2) factors and variables, (3) digital competence and teacher education, (4) students’ digital competence, and (5) digital competence and academic performance. The study also outlines seven future research directions: (1) integrating digital competence into curricula, (2) initial training in digital competence for future professions, (3) subject-specific development, (4) expanding research samples to include younger students, (5) addressing limitations of self-assessment, (6) understanding the needs of teachers and students, and (7) strengthening administrative support. Overall, the review highlights challenges in measuring digital competence and underscores the need for its integration into education systems, offering insights into opportunities for future research.